KOMPETENSI PROFESIONAL GURU TAMAN KANAK-KANAK DI KOTA PONTIANAK - Yuni, Dayang Uci Parida; Fadillah, Fadillah; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted to determine the professional competence of kindergarten teachers in Pontianak. The research method used was descriptive with a quantitative research form. The data source of this study was a kindergarten teacher. The sample used in this study was 78 kindergarten teachers with a certified civil servant status. The data collection techniques was indirect communication techniques with data collection tools in this study are questionnaires and documentation. Then, collected data was analyzed using quantitative data analysis techniques with central tendency formula Mean, Mode, and Standard Deviation. Based on the results of data analysis the professional competence of kindergarten teachers about learning mastery in Pontianak was in the category of